KEPRIBADIAN TOKOH ZAHRA DALAM NOVEL CINTA DALAM DIAM KARYA SHINEEMINKA (KAJIAN ANALISIS ISI) - Sumiharti Sumiharti; Rini Pudyastuti (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2022)
The Cinta Dalam Diam novel by Shineeminka is a novel that describes an arranged marriage that initially still accepts arranged marriages even though it is not based on love. The problem in this study is how the personality of the character Zahra in Shineeminka's novel Cinta Dalam Diam. The study aimed to describe Zahra's personality in Shineeminka's novel Cinta Dalam Diame. The methods used are descriptive qualitative. The results of the study based on the found 54 personality data of the main character. This includes id for about 9 data which expressed the urge to eat and drink, sex and resisting pain and discomfort, ego for about 29 which expressed  reasoning, problem solving and decision making, and a superego of 16 data covering shame, guilt. and a sense of regret. The most data is found in ego personality data while the least data is the superego.